IgM rheumatoid factor (RF), IgA RF, IgE RF, and IgG RF detected by ELISA in rheumatoid arthritis. Issue 1 (January 1987) - Gioud-Paquet, M; Auvinet, M; Raffin, T; Girard, P; Bouvier, M; Lejeune, E; Monier, J C
Abstract : One hundred patients with rheumatoid arthritis (RA), of whom 73 were seropositive by latex or Waaler-Rose (WR) assays, or both, 100 healthy subjects, and 102 diseased controls (22 patients with systemic lupus erythematosus (SLE) and 80 with bronchial asthma) were evaluated for the presence of IgM rheumatoid factor (RF), IgA RF, IgE RF, and IgG RF by an enzyme linked immunosorbent assay (ELISA). Ninety two per cent, 65%, 68%, and 66% of the patients with RA were found to be positive for IgM, IgA, IgE, and IgG respectively. A positive correlation existed between the levels of IgM RF and IgA RF on the one hand and disease activity on the other, and the levels of IgM RF and IgA RF correlated with the levels of circulating immune complexes as measured by a C1q binding assay. The presence of extra-articular features also correlated positively with the levels of IgA RF and IgE RF. Five out of six patients with Sjögren's syndrome had very high levels of IgA RF. Of 47 patients typed for HLA-DR, DR1 and DR2 were significantly more frequent in those with the highest levels of IgM RF. Conversely, DR3 was associated with low levels or absence of IgA RF and IgE RF. These results suggest that immune response genes may regulate the level of different RF isotypes. The frequencies of IgM, IgA, IgE, and IgG RF were 59%, 36%, 9%, and 27% respectively in SLE and 25%, 2.5%, 70%, and 59% in bronchial asthma.